Foundations of collective action in Asia: Theory and practice of regional cooperation - Amitav Acharya (Asian Development Bank Institute (ADBI), 2012)
This paper argues that the collective action in Asia by its regional organizations has historically suffered from a "capability-legitimacy gap": a disjuncture between the capability (in terms of material resources) of major Asian powers to lead regional cooperation on the one hand and their political legitimacy and will as regional leaders on the other. Successful collective action requires leadership with both capability (as suggested by rationalist theories) and legitimacy (as suggested by constructivist approaches). A central point of the paper is that the putative or aspiring leaders of Asian regionalism throughout the post-war period never had both. Actors who were materially capable of providing leadership and direction (the United States [US]1 and Japan) have lacked the necessary legitimacy, while those who have possessed legitimacy (India and the People's Republic of China [PRC])2 in the 1940s and 1950s, the Association of Southeast Asian Nations (ASEAN) since 1967, and Indonesia in the context of Asia as a whole) have lacked the necessary resources. The result has been that while the ASEAN-led Asian institutions have made a significant normative contribution to regional order, they have not proved to be effective instruments of regional problem solving. But the capability-legitimacy gap has both costs and benefits. While Asian regional institutions remain weakly institutionalized and attract criticism as "talk-shops", they have helped to ensure that Asia does not degenerate into a hegemonic order or a concert of power. It remains to be seen whether regionalism in an era of a rising PRC and India could bridge this gap. It is theoretically possible that the PRC and India could develop and possess both the resources and political will and standing to provide collective goods and lead Asian regionalism, but their mutual rivalry might prevent this.
Keywords: F50; F51; F53; F54; F55; F59; 330; asian regionalism; regional cooperation; asian regional cooperation; Regionale Wirtschaftsintegration; Internationale Zusammenarbeit; Asien